Hadith #2364 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Musayb bin Rafa'i al-Asadi المسيب بن رافع الأسدي الكاهلي أبو العلاء; Asim al-Ahwal عاصم الأحول; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Swa'a al-Khza'y Akhw Mghyth سواء الخزاعي أخو; Yahya bin Yaman al-Jly يحيى بن يمان العجلي (Sunan al-Nasa'i)
That the Messenger of Allah used to fast continually and it ws said that he would not break his fast, and he used not to fast and it was said that he would not fast.
Grade:

Hadith #2450 - Sunan Abi Dawud - Asim bin Abu al-Najud; Hafsa bint Umar; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Swa'a al-Khza'y Akhw Mghyth سواء الخزاعي أخو (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to fast three days every month.
Grade: Hasan